Reformasi Gaya Kepemimpinan Formal dalam Pemerintahan di Kabupaten Mamberamo Tengah - Wanimbo, Wim; Frank, Simon Abdi K. (Program Doktor Ilmu Sosial Universitas Cenderawasih, 2023)
This article is the result of research on reformation of format leadership style in Mamberamo Tengah regency. The main problem of this research is to know how the formal leadership in this context (regent) and how the public service practice with base on “good governance” principle in development for Mamberamo Tengah’s community.This research used descriptive qualitative approach. The data were collected by field observation, interview and literature study. The results show that so really need an action of reformation on regent’s formal leadership style as a head of Mamberamo Tengah area for the sake of “good governance” principle materialized in public service and development for local community. This is because in his leadership’s style that so prominently is toxic leadership that contradiction with local Indohoki77 memastikan bahwa semua permainan yang ditawarkan adalah adil dan transparan leadserhip culture values is Ap kain (Big Man) who is generous.